The Gender Reveal Party: A New Means of Performing Parenthood and Reifying Gender Under Capitalism - Jack, Astri (International Journal of Child, Youth and Family Studies, 2020)
This article explores the popularization of gender reveal parties and considers what they can tell us about current societal expectations around gender, parenthood, and consumption. Gender reveal parties are events in which expectant parents reveal, or even learn, the sex of the child-to-be through a surprise display of something pink or blue, typically using innocuous means such as confetti, balloons, or a coloured cake. However, methods for revealing fetal sex have become increasingly bizarre and dangerous, involving firearms, car fires, and, in at least one case, an alligator. This article examines digital media depictions of gender reveal parties and their aftermath; discusses sexing technologies and diversity in biological sex and gender; looks critically at how capitalism and the White neoliberal state have constructed the gender reveal party as a performative event for parents-to-be; and explores the physical and affective violence done to individuals, families, and the natural environment by gender reveal parties.